IDENTIFICATION OF PUBLIC MEDICINE STORAGE PROFILE IN THE COMMUNITY PHARMACY: A SYSTEMATIC REVIEW - Kadek Valentina Renita Dewi; Made Krisna Adi Jaya (Journal Pharmaceutical Science and Application, 2021)
Background: Drug is the most common form of therapy and an integral part of almost all levels of care. The conditions and proper way of storing medicines at home are important aspects of safe and effective drug treatment. Information about the knowledge of patients with appropriate storage conditions, rational drug use, appropriate drug use and management of various drugs is essential in helping pharmacists identify which medicinal products and aspects of home storage require more attention when counseling patients. Objective: The aim of this systematic review is to identify and characterize the mode of storage associated with home-stored pharmaceuticals. Methods: This systematic review analyzes the storage methods for medicines to identify and characterize the storage methods associated with medicines stored at home. The limitation of publication used, namely English and Indonesian in the last 10 years, and obtained through literature that can be considered relevant. Result: This systematic review was conducted in the period July, August, September 2020 - February 2021. As many as 20 journals were obtained. Those who met the inclusion criteria were 10 journals. Of the 10 journals that had met the inclusion criteria, 3 journals were excluded so that only 7 journals were used in literature review / systematic review.Storage of medicines in the household is based on the presence of family members who have certain diseases so that they have to consume drugs in the long term, the presence of health workers, and the education level of family members. Problems that can arise with drug storage conditions are impaired drug stability and can accelerate drug degradation prematurely. Storage of medicines in the medicine cabinet and out of reach of children is highly recommended. Placement of drugs in one place without being separated and a lack of awareness in administering specific markings can increase drug administration errors and lead to noncompliance with over-the-counter drug use. The application of drug management in the family can improve the quality of life and avoid the adverse effects of drug misuse. Conclusion: This study raises relation to medicines stored inside homes that warrant addressing that need pharmacists regarding public education in relation to drug therapy that goes beyond the dispensing process. Judging by the fnding that pharmacists were not considered primary sources of drug-related information. The good practices should be encouraged through continued health education at health institutions and medicine retail outlets. Keywords: Drugs; Storage; Household